16S RRNA METAGENOMIC ANALYSIS ON CAVENDISH BANANA (MUSA ACUMINATA AAA GROUP) RIPENING PROCESS WITH 1.25% CHITOSAN COATING: MICROBIOME ABUNDANCE AND FUNCTIONAL PROFILE - Fiola D M, Johanna
One of the challenges in the post-harvest management of banana is maintaining the product quality. As a climacteric fruit, bananas are known for their fast ripening process. One strategy to slow down the ripening process of bananas is using chitosan, which comes from the shells of marine animals such as shrimp or crab, as a coating. Chitosan has an antimicrobial effect that is thought to affect the microbiome community which plays a role in the ripening process of bananas. Several post-harvest related studies have shown that maturation events are controlled by various genes present in the host genome and the microbiome associated with that host. Therefore, this study aims to analyze the effect of chitosan coating on the microbial profile and predict its functional profile. The objects in this study were the peels and pulps of Cavendish banana cultivars (Musa acuminata cv. Cavendish AAA group) on the first and seventh day since the treatment was given in the form of 1.25% chitosan coating and non-chitosan as a control. Analysis of the microbial community was carried out using the metagenomic 16S rRNA amplicon sequencing and bioinformatics analysis was accomplished with the MOTHUR v.1.44.3 and Piphillin programs. Microbial abundance profiling showed that the community was dominated by Proteobacteria, Bacteroidota, Actinobacteria, and Firmicutes. Chitosan was found to inhibit the growth of the phyla Acidobacteriota, Bdellovibrionota, Deinococcota, Myxococcota, Planctomycetota, and Verrucomicrobiota on banana peels as well as the phyla Deinococcota, Dependentiae, and Planctomycetota on banana pulps. However, there were some microbial communities in bananas whose growth was not interrupted by the presence of chitosan. These microbes came from the phyla Actinobacteriota, Bacteroidota, Cyanobacteria, Firmicutes, and Proteobacteria. The functional profile analysis predicted the ripening pathways of bananas that were hindered by chitosan coating were arachidonic acid metabolism, sphingolipid metabolism, biosynthesis of N-glycans and O-glycans and proteasome activity. The results of the AMOVA (Analysis of Molecular Variance) statistical analysis showed that chitosan did not have a significant effect on the structural changes of the microbial community in bananas (p-value=0.136>? and p-value=0.734>?; ?=0.05).